Dimensional Accuracy of a Product Built Using Direct Metal Laser Sintering - Hanzl, Pavel; Zetková, Ivana; Kutlwašer, Jan (Manufacturing Technology Journal, 2018)
Direct Metal Laser Sintering (DMLS) is a method of Metal Additive Manufacturing which builds metal parts in a layer-by-layer procedure based on a CAD template. This method is diametrically different from machining methods such as turning or milling. Nowadays, DMLS is used for rapid manufacturing of complex metal parts. However, these products do not meet the requirements of high accuracy and surface quality. This paper deals with factors that are involved in the dimensional precision of DMLS production. The purpose of the Scale and Beam offset correction coefficients are described in the paper. Practical experiments and measurements were carried out and are presented here. Usual production accuracy was observed.
Keywords: Dimension Precision; Direct Melting Laser Sintering; Metal Additive Manufacturing; Selective Laser Melting